Initial investigation of molecular phenotypes of airway mast cells and cytokine profiles in equine asthma - Woodrow, Jane S.; Hines, Melissa; Sommardahl, Carla; Flatland, Bente; Lo, Yancy; Wang, Zhiping; Sheats, Mary Katie; Lennon, Elizabeth M. (Frontiers in Veterinary Science, 2023)
Equine asthma is a naturally occurring lung disease characterized by chronic, partially reversible airway obstruction, pulmonary remodeling, and lower airway inflammation. Asthma is currently divided into two major groups, mild to moderate asthma (mEA) and severe asthma (sEA), but further subtyping by phenotype (i.e. clinical presentation) and/or endotype (i.e. cellular mechanisms) may be warranted. For this study, we were interested in further investigation of cellular and inflammatory characteristics of EA, including airway mast cells. The purpose of this study was to: (1) compare mast cell protease mRNA expression between healthy and asthmatic horses, (2) analyze the cytokine profile present in BALF of currently defined equine asthma groups, and (3) use these data to evaluate potential biomarkers of defined asthma groups. We hypothesized that there would be significant differences in the cellular mast cell phenotypes (i.e. mucosal vs. connective tissue) and cytokine profiles in the BALF of asthmatic vs. healthy horses and across asthma groups. We assert these characteristics may inform additional subtypes of equine asthma. Adult horses were recruited from the institution’s teaching herd and clinical caseload. Mast cell protease gene expression of the BALF cellular component and multiplex bead immunoassay for cytokine concentrations in the BALF supernatant were investigated. Airway mast cells primarily expressed tryptase, with low levels of chymase. No significant changes in protease expression were detected across groups. Horses with severe asthma had increased TNF-α, CXCL-8, and IFN-γ concentrations in BALF supernatant. Multidimensional analysis demonstrated healthy and mEA horses have overlapping characteristics, with sEA separating from the other groups. This difference was primarily due to BALF neutrophil and lymphocyte concentrations. These study results further inform understanding of EA immunopathology, and future studies designed to investigate asthma phenotypes and endotypes. Ultimately, a better understanding of these groups could help identify novel therapeutic strategies.